Development of Multidisciplinary Competencies for the Young Generation through English Language Literacy, Digital Ethics, and Economic Literacy at PERMAI Pulang Penang, Malaysia - Syaila Syaila; Syawal Amirul Syah; Hikmawati Ribi; Andi Hakib; Kaswalia Kaswalia (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This community service program aims to develop the multidisciplinary competencies of young people through strengthening English literacy, digital ethics, and economic literacy. The program was conducted at PERMAI Pulau Pinang, Malaysia, involving 30 participants from the Indonesian diaspora community, including students and youth members. The implementation used participatory and educational approaches through interactive training, group discussions, and hands-on practice. The results indicate a significant improvement in participants’ understanding and skills, with an average post-training score increase of 80%. Participants demonstrated more effective English communication, ethical behavior in digital activities, and better financial management awareness. The multidisciplinary approach proved effective in shaping an adaptive young generation with strong ethical values and economic empowerment. This program serves as a model for empowering Indonesian diaspora communities to face the challenges of the digital transformation era.